2012
DOI: 10.1002/jmri.23818
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma in a North American population: Does hepatobiliary MR imaging with Gd‐EOB‐DTPA improve sensitivity and confidence for diagnosis?

Abstract: Hepatobiliary phase imaging may improve small lesion detection (<1 cm) and characterization of lesions in general, in MRI of the cirrhotic liver with Gd-EOB-DTPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 48 publications
3
52
0
Order By: Relevance
“…20,22 Previous studies showed improved diagnostic sensitivity/ PPV by adding HP images to dynamic MR imaging or by comparing them with CECT. 7,8,20,[23][24][25] Our results agreed with those of the previous studies. Using hypointensity as a major feature, we can more effectively categorize a hypovascular HCC of at least grade LR3.…”
Section: Discussionsupporting
confidence: 93%
“…20,22 Previous studies showed improved diagnostic sensitivity/ PPV by adding HP images to dynamic MR imaging or by comparing them with CECT. 7,8,20,[23][24][25] Our results agreed with those of the previous studies. Using hypointensity as a major feature, we can more effectively categorize a hypovascular HCC of at least grade LR3.…”
Section: Discussionsupporting
confidence: 93%
“…It has actually become common to encounter cases where hypervascular HCC or nodule-in-nodule HCC that is undetectable by MDCT is detected in a routine screening by EOB-MRI because of early enhancement in the arterial phase or clear hypointensity in the hepatobiliary phase [11,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103]. Furthermore, studies comparing the diagnostic performance of EOB-MRI and MDCT for hypervascular HCC have shown that EOB-MRI is superior or, at the very l...…”
Section: Diagnostic Algorithmmentioning
confidence: 99%
“…Until now, accumulating evidence has demonstrated that gadoxetic acid-enhanced MRI may provide better detection and characterization of HCCs compared with MDCT by permitting simultaneous evaluation of tumor vascularity as well as hepatocellular function [29,65,78,81,82,105,106,107,108,109,110]. Since OATP expression declines during hepatocarcinogenesis, approximately 88-95% of HCCs have low or no OATP8 expression and do not take up gadoxetic acid and therefore show hypointensity on hepatobiliary phase imaging [111,112].…”
Section: Diagnostic Criteriamentioning
confidence: 99%